2018
DOI: 10.1080/15384047.2018.1491490
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic drugs influence molecular mechanisms in prostate cancer

Abstract: Background: We investigated the role of diabetes mellitus (DM) and the molecular mechanisms of antidiabetic drugs in prostate cancer (PCa). Patients and Methods: 167 patients with both DM and PCa underwent radical prostatectomy (RPE). We divided our patient collective into "metformin" users, "insulin" users, "other antidiabetic drug" users and those with "no antidiabetic drug/diet only" (control group) and analyzed differences in PCa aggressiveness and laboratory parameters among treatment groups. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…MF is also used to treat non-alcoholic fatty liver disease [ 3 ], coronary artery disease [ 4 , 5 ], acute kidney injury and chronic kidney disease [ 6 ], in patients with T2DM, metabolic syndrome (MetS) and obesity, and in patients without apparent symptoms of metabolic disorders [ 7 ]. There are numerous clinical and experimental studies indicating the effectiveness of MF as an anticancer drug, used to prevent the growth and metastasis in breast cancer [ 8 , 9 ], endometrial cancer [ 10 , 11 , 12 ], colorectal cancer [ 9 , 13 ], prostate cancer [ 14 ] and in a number of the other tumors [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…MF is also used to treat non-alcoholic fatty liver disease [ 3 ], coronary artery disease [ 4 , 5 ], acute kidney injury and chronic kidney disease [ 6 ], in patients with T2DM, metabolic syndrome (MetS) and obesity, and in patients without apparent symptoms of metabolic disorders [ 7 ]. There are numerous clinical and experimental studies indicating the effectiveness of MF as an anticancer drug, used to prevent the growth and metastasis in breast cancer [ 8 , 9 ], endometrial cancer [ 10 , 11 , 12 ], colorectal cancer [ 9 , 13 ], prostate cancer [ 14 ] and in a number of the other tumors [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrate a persistently decreased risk of PCa for all anti-diabetic medications and durations. One possible explanation for this observation is that metformin and insulin are thought to reduce the activity of mTOR, which blocks progression of the cell cycle and cancer growth [26,27]. For example, Pircher et al conducted a study exploring antidiabetic drugs that influence molecular mechanisms in prostate cancer and showed that insulin use significantly decreased active mTOR in cancer tissue [26].…”
Section: Duration Of T2dm Medicationmentioning
confidence: 99%
“…One possible explanation for this observation is that metformin and insulin are thought to reduce the activity of mTOR, which blocks progression of the cell cycle and cancer growth [26,27]. For example, Pircher et al conducted a study exploring antidiabetic drugs that influence molecular mechanisms in prostate cancer and showed that insulin use significantly decreased active mTOR in cancer tissue [26]. In addition, they found an AMPK and AKT independent regulation of the mTOR pathway, as there were no differences in pAKT levels among treatment groups (insulin and metformin groups) [26].…”
Section: Duration Of T2dm Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrate a persistently decreased risk of PCa for all anti-diabetic medications and durations. Metformin and insulin reduce the activity of mTOR, which blocks progression of the cell cycle and cancer growth [26,27], giving a possible biological mechanism for the reduction in risk. However, other studies have shown no protective effect of metformin and insulin on PCa risk [14,[28][29][30].…”
Section: Duration Of T2dm Medicationmentioning
confidence: 99%